2012
DOI: 10.1148/radiol.12111148
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Whole-Body Total Lesion Glycolysis at Pretreatment FDG PET/CT in Non–Small Cell Lung Cancer

Abstract: Whole-body TLG is of prognostic value for NSCLC. It may be a promising tool for stratifying patients with NSCLC for risk-adapted therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

20
166
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(188 citation statements)
references
References 37 publications
20
166
2
Order By: Relevance
“…It is possible that once a lung tumour shows metastatic spread, the anatomic extent of the tumour is more important in predicting prognosis than the metabolic activity of the primary tumour only. Although this supposition should be confirmed with a larger number of patients with stage IV disease, this might be the reason why the introduction of other measures of metabolic activity such as tumour glycolysis and metabolic volume as well as heterogeneity and texture analysis are very promising as prognostic factors [44][45][46][47][48][49]. However, these "new" derived metabolic parameters seem to be more interesting in large tumours, due to the inability of PET to characterise tracer distribution within small tumours because of its limited spatial resolution.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that once a lung tumour shows metastatic spread, the anatomic extent of the tumour is more important in predicting prognosis than the metabolic activity of the primary tumour only. Although this supposition should be confirmed with a larger number of patients with stage IV disease, this might be the reason why the introduction of other measures of metabolic activity such as tumour glycolysis and metabolic volume as well as heterogeneity and texture analysis are very promising as prognostic factors [44][45][46][47][48][49]. However, these "new" derived metabolic parameters seem to be more interesting in large tumours, due to the inability of PET to characterise tracer distribution within small tumours because of its limited spatial resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Only recently has the prognostic value of TLG in NSCLC been elucidated (20)(21)(22). Chen et al (20) demonstrated that a whole-body TLG is a potentially useful indicator for PFS in NSCLC, because a high whole-body TLG (.655) is associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…For non-small cell lung cancer (NSCLC), 18 F-FDG PET/CT image quantification has been shown to provide prognostic information. PET image-derived features, including metabolically active tumor volume (MATV), mean standardized uptake value (SUV mean ), and total lesion glycolysis (TLG, defined as MATV · SUV mean ), have been shown to provide an accurate assessment of tumor burden with potentially higher prognostic value than standard maximum SUV (SUV max ), for both surgical and nonsurgical patients (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%